Surgical Treatment of a Giant Pleomorphic Adenoma of the Submandibular Gland: A Case Report - Wu, Zehui; Liu, Defeng; Peng, Shihao; Wang, Yuejun; Zhan, Xiaolin; Li, Laibin; Wan, Hong; Li, Yangyang; Guo, Tao; Xu, Aman (Frontiers in Surgery, 2022)
Pleomorphic adenomas (PAs) are the most common benign salivary neoplasms. PAs are generally slow-growing but may sometimes become aggressive and grow rapidly within a short period of time. Here, we report the case of an 83-year-old Chinese woman with an anterior neck mass that had been growing over the past 30 years. She felt uncomfortable because the mass had grown quite rapidly in the past year. The final diagnosis of a PA of the left submandibular gland was confirmed by histopathological and immunohistochemical examinations after surgical resection. Our patient recalled a history of an excision of a neck mass 40 years prior to presentation at another hospital. Based on our imaging findings and surgical findings, we speculate that the neck mass 40 years prior may also have been a PA. Our case reminds us the rare recurrence possibility of PAs, and early and thorough resection may have a good prognosis. In addition, to the best of our knowledge, this is the largest PA of the submandibular gland reported to date.